2004
DOI: 10.1111/j.1467-842x.2004.tb00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Folate promotion in Western Australia and the prevention of neural tube defects

Abstract: Objectives: We conducted a case-control study to investigate the effectiveness of effor ts to increase folate intake in Western Australia (WA) for the prevention of neural tube defects (NTD). Methods: Case (36) and control (578) mothers completed questionnaires, from which their intake of folate from supplements and food (including fortified foods) was estimated.Results: Almost one-third of women took folic acid supplements periconceptionally.Supplement use was associated with a non-significant 4% reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 25 publications
3
37
0
Order By: Relevance
“…27 Less than half of women surveyed in each State took periconceptional folate supplements. This finding is consistent with published studies based on Australian and overseas hospitalor service-based samples, 9,10,15,18,[28][29][30][31][32][33] and with US populationbased data. 11,12 Factors associated with not taking PFS, as in other populationbased studies, 11,12 are: being less than 25 years of age, having less education, being unmarried, having low family income, being born in non-English speaking countries, and unplanned pregnancy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…27 Less than half of women surveyed in each State took periconceptional folate supplements. This finding is consistent with published studies based on Australian and overseas hospitalor service-based samples, 9,10,15,18,[28][29][30][31][32][33] and with US populationbased data. 11,12 Factors associated with not taking PFS, as in other populationbased studies, 11,12 are: being less than 25 years of age, having less education, being unmarried, having low family income, being born in non-English speaking countries, and unplanned pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…The current habitual dietary intake of folate for most Australian women is well below that recommended for risk reduction of NTDs. 8,9 Primary prevention strategies to reduce the risk of NTDs include: periconceptional intake of folic acid supplements, increased consumption of foods naturally high in folate, and fortification of staple foods.A recent systematic review of periconceptional folic acid use based on studies conducted between 1992 and 2001 found periconceptional supplement use of between 0.5% and 52%. 10 Three studies drew on population-based samples (two using data from the United States Pregnancy Risk Assessment Monitoring System (PRAMS) 11,12 ) and the other, a South Australian study, also reported hospitalbased data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There was high participation in our study (79%) but non-responders were more likely to be young, unmarried, not to have private health insurance, to smoke during pregnancy, and have either had no previous births or more than two previous births 15 . With the exception of women with two or more previous births, all of these characteristics were associated with a greater risk of not knowing the correct message and not taking periconceptional folic acid supplements 20 .…”
Section: Discussionmentioning
confidence: 85%
“…Information collected from the long and short questionnaires included: awareness of the main health message about folate and spina bifida and timing of awareness of this message 15 ; and awareness of folate fortification measured as (1) awareness of folate added to foods, (2) knowledge of folate labelling of foods and (3) how often labels were read. We measured the proportion of women who noticed any labels on foods that mentioned folate, whether they were aware that folate was added to foods, how often they read the labels on foods and packaging, what foods they were aware of that had folate added to them, if they ate folate-fortified food, and if so, how much of the fortified food was eaten in the six months before their recent pregnancy.…”
Section: Data Collectionmentioning
confidence: 99%